Peran Sumsel Independen Dalam Membangun Literasi Media Tentang Isu Pendidikan Bagi Pembaca - Ahmad Said; Nuraida .; Jufrizal . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This research is entitled "The Role of Independent South Sumatra in Building Media Literacy on Educational Issues for Readers." The problems studied in this research include how Independent South Sumatra plays a role in improving media literacy and how journalist literacy is applied in presenting news related to educational issues. This research aims to identify and analyze the contribution of media in improving readers' media literacy through the presentation of educational news. The method used is a qualitative approach with a descriptive research type. Data collection was carried out through interview techniques, observation, and documentation. The research informants consisted of one editor-in-chief and four journalists from Independent South Sumatra. The data analysis process was carried out through the stages of data reduction, data presentation, and drawing conclusions. This research uses the media literacy theory from James W. Potter which includes four main components, namely knowledge structures, personal locus, skills, and information processing. This theory is used as a basis for examining the role of journalists and the media in building media literacy through reporting. The results of the study indicate that Independent South Sumatra has carried out its role in improving media literacy by presenting news that is informative, educational, and relevant to educational issues. Journalists have also implemented media literacy principles in their reporting, such as verifying information, delivering balanced news, and encouraging readers to be critical. However, several obstacles remain, including time constraints and the need for speed in news production